2015
DOI: 10.1097/ypg.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Gene–environment interactions in psychopathology throughout early childhood

Abstract: Up to 20% of children and adolescents worldwide suffer from mental health problems. Epidemiological studies have shown that some of these problems are already present at an early age. The recognition that psychopathology is a result of an interaction between individual experiences and genetic characteristics has led to an increase in the number of studies using a gene-environment approach (G×E). However, to date, there has been no systematic review of G×E studies on psychopathology in the first 6 years of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…A prevailing theory of neurodevelopmental pathogenesis is that environmental factors and genetic predisposition converge to disrupt neural circuits controlling social, emotional, and cognitive behavior [1],[2],[3],[4]. An environmental factor that could impair neurodevelopment is maternal obesity, as one third of women in the United States are obese [5].…”
Section: Introductionmentioning
confidence: 99%
“…A prevailing theory of neurodevelopmental pathogenesis is that environmental factors and genetic predisposition converge to disrupt neural circuits controlling social, emotional, and cognitive behavior [1],[2],[3],[4]. An environmental factor that could impair neurodevelopment is maternal obesity, as one third of women in the United States are obese [5].…”
Section: Introductionmentioning
confidence: 99%
“…Common mental disorders include bipolar disorders (manic disorder, depression, and manic-depression), dementia, schizophrenia, and panic disorder [ 2 ]. Several factors affecting the development of mental disorders include genetic factors, stress, diet, physical inactivity, drugs, and other environmental factors [ 3 4 5 ]. Among these factors, dietary factors may aggravate or ameliorate symptoms and the progression of the disorders although those are not major etiologies.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, maternal gene variants may unbalance the in utero folate isoform availability and alter fetal hematopoiesis. In several investigations, it has been demonstrated that among case mothers but not among fathers or affected children, folate gene variants were associated with child anomalies as pediatric anencephaly, Down syndrome, autism, or brain defects, and this strongly fits with the in utero origin hypothesis of childhood ALL [6,63,64].…”
Section: Discussionmentioning
confidence: 69%